Family Contribution to Social Interaction Behavior of Down Syndrome Children - Yanti Suryanti; Mohammad Taufiq Rahman (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2023)
The research objectives were to discover the social behavior built between the family environment and children with Down syndrome and to know the social interactions of children with Down syndrome with family, friends, schools, and the community. The theory used in this study is the theory of Symbolic Interactionism, which considers structural factors, namely society. According to Mead's observations, the concept of self, which he refers to determines the will, desires, and ambitions of human beings, also has a conception that considers the circumstances around them. Always influenced by internal interactions associated with the state of society. This study uses a descriptive method with qualitative data types. This research is located in Cibeureum Village, Kertasari District, Bandung Regency. The researcher chose this location because it is close to where the author lives, so it can facilitate research in obtaining research data. The subject of this research is family. The results of this study indicate that the family environment is seen as the main determining factor in child development. Therefore, the family's contribution to parenting children with Down syndrome must be well established. Good socialization will make it easier for children to adjust to society later.